Penerapan Software Rategain dalam Efektivitas Kerja pad Sales and Marketing Departement di Fame Hotel Sunset Road Legian Kuta Bali - Wiguna, Adhi Karya; Widiatmaja, I Gusti Ngurah; Suarka, Fanny Maharani (Jurnal Kepariwisataan dan Hospitalitas; Vol 7 No 2 (2023): Vol.7,No.2,2023, 2023)
This research discusses RateGain software in its application at Rate gain software application for  effectivity working sales n marketing staffs  at  Fame Hotel Sunset Road Legian, Kuta, Bali. However, in terms of the quality of work of employees in using the Rategain software, it is not known how effectively the employees work, according to employees of Rategain Dode Hoki Mokarisma said "this application makes users easily access the latest market news and makes it easier with other online travel agents . This has affected hotel performance given the fast growing market through the internet. Researchers want to know what problems occur in operating the Rategain software in the quality of work at Fame Hotel. And from the data sources above, it can be seen that Rategain prioritizes customer satisfaction and makes promotions from a hotel increase so that the income earned automatically increases. This makes the writer want to know the increase experienced by hotels that have used Rategain. Rategian in the daily activities of employees in operating the software, as well as how the effectiveness of employees work since the implementation of RateGain software at Fame Hotel Sunset Road Legian, Kuta, Bali. This   research aims to find out how rategian software is implemented in employees' daily life in improving software, as well as how effective employees work since the implementation of RateGain software at Fame Hotel Sunset Road Legian, Kuta, Bali. Sample determination technique using Purposive Sampling In this study the sample seduction criteria are employees of Sales & Marketing or employees of Sales & Marketing of Fame Hotel Sunset Road”. “There are a total of 7 employees from Sales & Marketing from Fame Hotel Sunset Road”. “The analysis techniques used are quantitative deskritype, qualitative deskritype, and likert scale. The results of this study are known that the application of RateGain software in hotel revenue that already uses RateGain software. Revenue surged because sales and marketing did not take long to change sales strategy through RateGain system. And the effectiveness of employees' work in using Rategain software increases due to Accurateness Understandability and Operability. When the reign time of the use of RateGain is faster in carrying out the work, then the effectiveness of the work will increase. Sales and marketing workers feel the main impact of the use of the system is the function of the system in terms of Fault tolerance and Stability”